Risk Factors for Stunting Among Children Under Five Years of Age in The Kokoda Tribe, Sorong City - Radeny Ramdany; Norma (Jurnal Ilmiah Kesehatan, 2023)
Stunting is a chronic nutritional deficiency resulting in short stature and cognitive impairment. Sorong City has the highest incidence of very short and short toddlers in West Papua Province, 52.58%. This study analyzes the risk factors for stunting among children under five years of age in the Kokoda tribe, Sorong City. This study used a case-control design. The population was all parents and children aged 12-59 months registered at Integrated Health Post in 8 selected villages in Sorong City in 2021, totaling 1,890 children. There were 168 samples, 84 in the cases group and 84 in the control group, with the purposive sampling technique. Data collection used a stunting risk factors questionnaire on toddlers and measured body length, weight, and upper arm circumference. The data was processed by analyzing the Odds Ratio (OR) with the SPSS application. Results showed that children with birth lengths less than 48 centimeters had a 2.652 times greater risk of experiencing stunting compared to those more than equal to 48 centimeters. Children with birth weight less than 2,500 grams had a three times greater risk of stunting compared to those more than equal to 2,500 grams. Respondents with no clean water availability had 2.013 times more experienced stunting. Mothers not taking iron supplements during pregnancy could increase the risk of stunting three times. The risk factors for stunting among under-five children in the Kokoda tribe, Sorong City, are birth length, birth weight, the availability of clean water, and iron supplements during pregnancy.